Exploring Protein Supplements: Benefits, Risks, And Implications For Health- A Review (International Journal of Environmental Sciences, 2025)
Protein supplements have become a cornerstone in the modern health and wellness landscape, widely utilized by athletes, fitness enthusiasts, and individuals seeking efficient ways to meet dietary protein requirements. These products are celebrated for their contributions to muscle development, post-exercise recovery, and weight management. However, their growing popularity has raised concerns regarding potential health risks, especially when consumed excessively or without proper guidance. Over-reliance on protein supplements can lead to adverse effects such as kidney strain, cardiovascular issues, and exposure to contaminants like heavy metals. This review provides a comprehensive analysis of the different types of protein supplements, including whey, casein, plant-based, collagen, and specialized blends, highlighting their distinct benefits and associated risks. Additionally, it delves into the challenges posed by inadequate regulatory oversight and the implications for product safety and consumer health. Emerging trends in the industry, such as sustainable protein sources and personalized nutrition, are also discussed, offering insights into the future of protein supplementation. The objective of this review is to present a balanced understanding of how to maximize the advantages of protein supplements while mitigating their potential health hazards. By emphasizing informed usage and advocating for stricter quality control measures, this study aims to contribute to the responsible consumption of protein supplements, fostering better health outcomes and sustainability in dietary practices.